SPATIAL CONCEPTS OF STAIRCASES IN TRADITIONAL MACEDONIAN ARCHITECTURE OF THE 19TH CENTURY - Temelkovski, Branko (Faculty of Design and Technology of furniture and interior – Skopje, 2022)
The staircase in traditional Macedonian architecture from the 19th century, apart from being a functional object, also appears as a strong visual and sculptural motif in a complex spatial system. It is also an indispensable segment of the "spatial path" as named by Grabrian (1986). The aim of this research is to explore the spatial features of staircases in traditional Macedonian architecture from the 19th century. For this purpose, the research was conducted as a systematic study of staircases in buildings with 3 or more levels, i.e. buildings with two or more sets of stairs. These objects are specific in their complex spatial arrangements. The research was conducted on 72 houses from different parts of Macedonia - Veles, Galichnik, Debar, Kochani, Kratovo, Krushevo, Lazaropole, Ohrid, Struga, Strumica and Tetovo. As a result of the analysis performed, staircases were typologically classified according to: their positioning in the plan, the path of movement, and contradictions in spatial arrangement.
Keywords: stairs, path, spatial arrangement, traditional architecture